The Role of Unions in Inflation: A Survey Article - Williams, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
Wide divergence of views exists on the power of unions to influence the general wage level. This paper contrasts selected views. A modified Trevithick/Mulvey classification of union reaction to escess demand for labour is used to classify writers. A second part examines questions of union power and militancy.